Estimating the impact of co-investment in fiber to the home coverage - Marc Lebourges; Julienne Liang (International Telecommunications Society (ITS), 2018)
Does co-investment enhance fiber to the home (FTTH) coverage? We combine several French municipality-level datasets to answer this question. We find that a 1% co-financing share by co-investors leads to an increase in FTTH coverage by 0.8% during the 2013-2016 study period and a 0.6% annual progression. This result is robust to changes in the specification and instrument and is consistent with the outcome of a simple difference-in-differences analysis comparing FTTH coverage in co-investment areas with areas with no co-investment ceteris paribus. In addition, we find that a 1% co-investment increases FTTH adoption among Orange's fixed broadband customers by 1.2% and decreases Orange's total fixed broadband penetration for asymmetric digital subscriber lines (ADSL) plus FTTH coverage by 1.1%, which benefits competitors. Our findings confirm that co-investment supports the policy objectives of coverage, adoption and competition and should be supported by regulation.
Keywords: L43; L51; L96; 330; FTTH coverage; co-investment